Entrepreneurship Development Model in Higher Education - Anjali Marwiyah Siregar; Zuhrinal M. Nawawi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
The lack of entrepreneurs in Indonesia demands the role of campuses in motivating undergraduates to become entrepreneurs. The Ministry of Cooperatives and SMEs said that Indonesia needed around 20 million new entrepreneurs. With the increase in entrepreneurs from undergraduate circles, it will reduce the increase in the number of unemployed and even increase the number of jobs. To develop an entrepreneurial culture among the academic community, a model is needed. The model in question is not only based on the scientific potential inherent in entrepreneurship itself (theory) and students as subjects but also its relation to UKMKM including government and private institutions. The relationship between the three will be the axis of change in college graduation.